DEKONSTRUKSI SISTEM PENDIDIKAN FORMAL DAN MASYARAKAT TANPA SEKOLAH DALAM PANDANGAN IVAN ILLICH - Siswadi, Gede Agus (Jawa Dwipa, 2024)
Education, as the main pillar in the development of individuals and society, should be a means to develop the full potential of human beings and inspire holistic growth. However, various forms that lead to dehumanisation have occurred in the system of education, especially formal education in schools. This research aims to explore Ivan Illich’s views on liberating society from the shackles of schooling. Ivan Illich, a critical thinker in the field of education, proposed the concept of a deschooling society as an alternative to the conventional formal education system. Through his critical approach, Illich identified the negative impacts caused by formal education institutions, including the limitation of individual potential, monopoly of knowledge, and inequality of access to education. This research uses a qualitative method with a philosophical hermeneutic approach. The results of this study show that Illich emphasises the need to free education from conventional boundaries, encouraging social inclusion, independence, and creativity in learning. Moreover, his concept of a deschooling society offers a more inclusive and democratic alternative, allowing individuals to learn according to learner’s interests and needs. In addition, Illich formulated alternative education by providing a learning webs system as an education system that is less tied to formal education in schools.